SIGNIFICANCE OF INTENSITY OF SWEDISH MASSAGE COURSE IN IMPROVEMENT OF HEALTH STATUS - Veseta, Una; Gulbe, Antra; Onževs, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the study is to compare the immediate and cumulative effects of Swedish massage on the physiological, emotional, and biochemical factors of healthy individuals, as well as the sustainability of the effects depending on the intensity of the course.The study subjects were 30 healthy young women. The subjects were randomly assigned into two groups. Subjects got in total ten Swedish back massages: twice and once a week. At the research the complete blood count was performed, salivary cortisol level, total antioxidant capacity were checked with the resources of laboratory “E.Gulbja Laboratorija”(www.egl.lv) Emotions were tested by using the FaceReader 6.0™. Body composition analysis was performed by using Tanita SC 330, blood pressure and heart rate were also measured (Omron M7–IT). The collected data was analyzed by using methods of mathematical statistics. Regression testing was performed by using the Fisher criterion. Analysis of the obtained data allows us to observe positive trends in Swedish massage to the improvement of health status. Differences in some summary results of massage effects were identified.